(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the process and conditions for the synthesis of porous silica materials based on alkoxysilanes and metal oxides are studied. the main stages are discussed. A change in the pH value of a solution affects the relative rate of hydrolysis and condensation reactions of the solution, which makes it possible to obtain various structures from weakly branched silicate polymers to ordered, densely packed particles. The H2O/TEOS molar ratio (R) also has a significant effect on the structure of the synthesized silica materials. By changing R, silica materials can be obtained in the form of solid gels and colloidal particles. The composition and properties of the developed gas sensitive materials were studied by SEM, XRD and thermal analysis.